TINJAUAN POTENSI OBJEK WISATA PANTAI TUGU JEPANG AIR BANGIS KECAMATAN SUNGAI BEREMAS MENJADI DESTINASI WISATA KABUPATEN PASAMAN BARAT - Warni, Nelli; Silfeni, Silfeni; Chair, Ira Meirina (Journal of Home Economics and Tourism, 2015)
This research is motivated not influx attraction Tugu Jepang Air Bangis Beach into 10 major destination attractions in West Sumatra. This research aimed to describe potential of Tugu Japan Air Bangis Beach which include (a) what to see, (b) what to do, (c) what to buy, (d) what to arrived and (e) what to stay. This type of research is qualitative descriptive. The data of this research is the potential attraction of Pantai Tugu Jepang Air Bangis. Techniques of collecting data using interviews, observation and documentation involving informants namely attraction manager (5 people), traders around attractions (7 people), as well as visitor attractions (10) using Snowball sampling technique. results of the research are Tugu Japan Air Bangis Beach no fit into 10 major destination attractions Â West Sumatra. It is seen by 5 main condition Tugu Japan Air Bangis Beach tourism destination not meet these requirements to the maximum five. The fifth requirement is already there but is still inadequate. Â Keyword : Potensial, Tourist Objects, Tour Destination